Management of Broodstock Rearing of Vanname Shrimp (Litopenaeus vannamei) at PT Esaputlii Prakarsa Utama, Barru Regency, South Sulawesi - Ratnawati; Siska Sarmayani; Subhan Effendi; Ilham Ahmad (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of writing this final project is to find out how to manage the maintenance of vannamei shrimp (Litopenaeus vannamei) properly. The types of data used in collecting the required data include primary and secondary data.The data analysis method used to determine the management of vannamei shrimp broodstock (Litopenaeus vannamei) is qualitative descriptive data analysis. Held from January to April 2022 at PT Esaputlii Prakarsa Utama (benur kita) Barru Regency, South Sulawesi. The result of this Final Project is the acceptance of broodstock consists of preparation of brood acclimatization maintenance room and preparation of acclimatization basin, brood selection, acclimatization, brood maintenance consists of tub preparation, brood maintenance basin water filling and ablation management, circulation in the brood rearing basin of vannamei shrimp (Litopenaeus vannamei), gonad maturity level, sampling of mated brood, feed management, egg management including egg hatching, The harvest of naupli is up to the counting of naupli